Positive surgical margins and their locations in specimens are adverse prognosis features after radical cystectomy in non‐metastatic carcinoma invading bladder muscle: results from a nationwide case–control study. (17th January 2013) - Neuzillet, Yann; Soulie, Michel; Larre, Stéphane; Roupret, Morgan; Defortescu, Guillaume; Murez, Thibaut; Pignot, Géraldine; Descazeaud, Aurélien; Patard, Jean‐Jacques; Bigot, Pierre; Salomon, Laurent; Colin, Pierre; et al.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Positive surgical margin (PSM) frequency after radical cystectomy has been estimated to be 4–15%. Studies that have not distinguished between the different sites of PSM have failed to show that they are an independent prognostic factor for disease‐free survival. Only perivesical soft tissue PSMs have been associated with an increased risk of cancer recurrence and cancer‐specific death. This is the first comprehensive published analysis of PSMs occurring during radical cystectomy for pTx pN0 M0 bladder cancer according to their location, comparing their cancer‐specific survival (CSS) and other outcomes with those of a control group paired according to TNM status, age, sex and urinary diversion method. Local recurrence‐free survival rates were found to be lower in patients with both soft tissue and urethral PSMs. Moreover, soft‐tissue PSMs were associated with lower metastatic recurrence‐free and CSS rates. Objective To compare the prognoses associated with positive surgical margins (PSMs) according to their urethral, ureteric and/or soft tissue locations in patients with pN0 M0 bladder cancer who have not undergone neoadjuvant chemotherapy. Patients and Methods A retrospective, case–control study was conducted between 1991 and 2011 using data from 17 academic centres in France. A total of 154 patients (cases) with PSMs met the eligibility criteria and were matched according to centre, pT stage, gender, age and urinary diversion method with a population‐based sample of 154 patients (controls) from 3651 patients who had undergone cystectomies. The median follow‐up period was 23.9 months. Multivariable Cox regression analysis was used to test the effects of PSMs on local recurrence (LR)‐free survival, metastatic recurrence (MR)‐free survival and cancer‐specific survival (CSS). Results The 5‐year LR‐free survival and CSS rates of patients with urethral and soft tissue PSMs were lower than those in the control group. A significant decrease in CSS was associated with soft tissue PSMs (P = 0.003, odds ratio = 0.425, 95% confidence interval 0.283–0.647). The prognosis was not affected in cases of ureteric PSMs. Conclusions Soft tissue PSMs were associated with poor CSS rates in patients with pN0 M0 bladder cancer. A correlation between urethrectomy and a reduction of the risk of LR in a urethral PSM setting was observed.